1986
DOI: 10.1103/physrevlett.57.3257
|View full text |Cite
|
Sign up to set email alerts
|

Octupole deformation in neutron-rich barium isotopes

Abstract: Partial decay schemes for the very neutron-rich nuclei '4 '~Ba and ' Ba have been determined by the study of y-y coincidences in 5 Cf fission fragments. Interlaced positiveand negative-parity levels connected by fast electric dipole transitions are observed in '~Ba and ' Ba above spin 7A. This is similar to the situation in some light actinide nuclei, where the data have been interpreted in terms of reflection-asymmetric shapes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
113
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 239 publications
(131 citation statements)
references
References 8 publications
12
113
0
Order By: Relevance
“…The evolution of quadrupole deformation and the presence of the octupole collectivity in the barium isotopes have attracted much attention both experimentally and theoretically [1][2][3][4][5][6]. As expected, quadrupole deformation was found to increase gradually with decreasing neutron number from the spherical N = 82 semi-magic nucleus 138 Ba to the N = 66 midshell isotope 122 Ba.…”
Section: Introductionmentioning
confidence: 96%
“…The evolution of quadrupole deformation and the presence of the octupole collectivity in the barium isotopes have attracted much attention both experimentally and theoretically [1][2][3][4][5][6]. As expected, quadrupole deformation was found to increase gradually with decreasing neutron number from the spherical N = 82 semi-magic nucleus 138 Ba to the N = 66 midshell isotope 122 Ba.…”
Section: Introductionmentioning
confidence: 96%
“…Following the development of large detector arrays, much progress has been made in investigating the high spin states in these neutronrich nuclei. In previous experimental studies, octupoledeformed bands and strong octupole correlations have been observed in many nuclei in this region, especially in Z = 56 Ba and Z = 58 Ce neutron-rich isotopes, such as, in 140−146,148 Ba [3][4][5][6][7][8], 144,146,148 Ce [3,5,[9][10][11][12] by measuring the prompt γ-rays from the spontaneous fission of actinide nuclei.…”
mentioning
confidence: 77%
“…The relation between ϑ and gamma energy E is given by [26]: (12) and the relation between E and is given by [27]:…”
Section: Methods and Calculationsmentioning
confidence: 99%
“…The ground-state band GSB with I π =0+, 2+, 4+, ..., and the negative parity band NPB with I π =1 − , 3 − , 5 − .... in even-even nuclei are interwoven, forming a single octupole band with levels characterized by I π =0+, 1−, 2+, 3−, 4+, .... [12][13][14][15][16][17]. This is an example of odd-even staggering or I=1 staggering; the latter term being due to the fact that each energy level with angular momentum I is displaced relatively to its neighbors with angular momenta I= 1 [15].…”
Section: Introductionmentioning
confidence: 99%